Marikina City business and innovation center - Balaccua, Nadine Isabela D.; Yazon, Rizalino O. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
Marikina City used to be generally residential but is now considered one of the developing cities in Metro Manila because of its increasing economic opportunities. The proposed project aims to support and promote the trade of local crafts and business by providing offices and commercial spaces to incubate them and a platform where they can exhibit their products and services to the public. But due to the influx of people from different areas, commercialization usually results to diminishing cultural values of the city. The project aims to provide a structure that will focus in the revitalization and preservation of the community's cultural activities. With its functionality and visual identity, the proposed project is intended to become a cultural icon and an urban catalyst for the city.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman